Prekmurska publicistika 19. in prve polovice 20. stoletja - med knjižno normo in tradicijo - Jesenšek, Marko (Slavistična revija, 2008)
In Prekmurje, the switch from the literary norm to dialect first occurred in the first Prekmurje newsletter Prekmurje Prijatel. In the 20th century, it is observed also in Marijin list, in Ka/endar srca Jezusovega and in Novine. The first issues in the early years of these publications strictly adhere to the traditional Prekmurje literary norm, later however, they are faced with the new Slovenian language, gradualomission of the linguistic norms, intrusion of dialectal elements into journalistic language and, in the period between the two worlds wars, the adoption of a unified Slovenian literary norm.
Keywords: Prekmurje; publicistični jezik; slovenščina; zgodovina jezika